Proceedings of the 4th International Congress on Sport Sciences Research and Technology Support 2016
DOI: 10.5220/0006079400150024
|View full text |Cite
|
Sign up to set email alerts
|

Objective Classification of Dynamic Balance Using a Single Wearable Sensor

Abstract: Abstract:The Y Balance Test (YBT) is one of the most commonly used dynamic balance assessments in clinical and research settings. This study sought to investigate the ability of a single lumbar inertial measurement unit (IMU) to discriminate between the three YBT reach directions, and between pre and post-fatigue balance performance during the YBT. Fifteen subjects (age: 23±4, weight: 67.5±8, height: 175±8, BMI: 22±2) were fitted with a lumbar IMU. Three YBTs were performed on the dominant leg at 0, 10 and 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…These range from early stage rehabilitation exercises such as heel slides and straight leg raises [ 12 ] to more complex S&C exercises such as bodyweight squats [ 14 ], lunges [ 15 ], and single-leg squats [ 13 , 16 , 17 ]. More cost-effective and practical systems using a single body-worn IMU have also been shown to be effective in the analysis of exercise technique [ 13 , 15 , 18 , 19 ]. Such single IMU-based systems are considered preferential where they can provide equivalent exercise analysis quality to multiple IMU setups.…”
Section: Introductionmentioning
confidence: 99%
“…These range from early stage rehabilitation exercises such as heel slides and straight leg raises [ 12 ] to more complex S&C exercises such as bodyweight squats [ 14 ], lunges [ 15 ], and single-leg squats [ 13 , 16 , 17 ]. More cost-effective and practical systems using a single body-worn IMU have also been shown to be effective in the analysis of exercise technique [ 13 , 15 , 18 , 19 ]. Such single IMU-based systems are considered preferential where they can provide equivalent exercise analysis quality to multiple IMU setups.…”
Section: Introductionmentioning
confidence: 99%
“…This may be applied in clinical practice through long-term tracking of injury/ pathology risk, recovery and response to interventions. For example, fatigue has been shown to negatively influence PC performance [15,16], potentially increasing an individual's propensity to injury [17]. As such, longitudinal monitoring paradigms may be used to model an individual's 'normal' PC, with large alterations outside of an acceptable range aiding in the identification of those who may be at an increased risk of pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies assessed discriminant validity in healthy cohorts, assessing the ability of inertial sensor systems to discriminate between known stance, visual, hearing, fatigue or taping conditions [25,28,32,41,[43][44][45][46][47][48][49][50].…”
Section: Discriminant Validity -Healthy Populationmentioning
confidence: 99%
“…Two studies investigated the ability of a lumbar mounted sensor to differentiate fatigue and nonfatigued dynamic PC performance during the YBT. Johnston et al [49] demonstrated that a machine learning approach can classify PC performance with 61.9 -71.4% accuracy, and differentiate YBT reach directions with 97.8% accuracy. Additionally, Johnston et al [45] reported significant differences between fatigued and non-fatigued performance, capturing alterations in balance not detected by the traditional measure, suggesting greater sensitivity.…”
Section: Discriminant Validity -Healthy Populationsmentioning
confidence: 99%